СОВЕРШЕНСТВОВАНИЕ НАУЧНО - ИССЛЕДОВАТЕЛЬСКОЙ КОМПЕТЕНТНОСТИ СТУДЕНТОВ ПРИ ОБУЧЕНИИ АНГЛИЙСКОМУ ЯЗЫКУ В ВЫСШИХ УЧЕБНЫХ ЗАВЕДЕНИЯХ - Бурибаева, А.И. (SCIENCE and SOCIETY, 2020)
The article highlights the issues based on improving the research competence of students in teaching English in higher educational institutions.